Kesetaraan Gender tentang Kepemimpinan Perempuan di Lingkungan Kampus IAIN Syekh Nurjati Cirebon Menurut Perspektif Hadis Shahih Bukhari - Aisyah Aisyah; Hartati Hartati; Umayah Umayah; Indra Gunawan; Aah Syafa’ah (Gunung Djati Conference Series, 2023)
The purpose of this study is to discuss gender equality regarding women's leadership in the IAIN Syekh Nurjati Cirebon campus environment according to the perspective of authentic Bukhari hadith. The method used in this research is literature study and field study. The research resulted in findings that in the campus environment IAIN Syekh Nurjati has implemented gender equality with examples of female leaders in the campus leadership structure or student organizations. This is in line with the authentic hadith of Bukhari regarding women's leadership explaining that this hadith has a special meaning if it is aligned with asbabul al-wurud because the incident occurred in ancient times with conditions that are of course different from today.